Skin Temperature Distribution over Human Head Due to Handheld Mobile Phone Call using Thermal Imaging Camera - Khaleel, Yazen A.; Yahya, Salah I.; Ibrahim, Rahel Kh. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
The possible biological hazards due to the mobile phone electromagnetic (EM) field exposure are caused mainly by a temperature rise in tissue. Hence, the calculation of temperature in tissue may be more realistic than the calculation of specific absorption rate (SAR) due to the more direct relationship between temperature and safety. The heat transfer to human tissue due to a phone call is caused by a combined effect of conductive heat transfer caused by the basic non-microwave-related activity of the mobile phone and the absorption of the microwave. This paper investigates the role of heat transfer in living tissue due to thermal conduction. This is achieved using a thermal imaging camera to measure and map the skin temperature distribution over human head due to mobile phone EM emission. Two commercial mobile phone brands, that is, Apple iPhone 7 Plus and Huawei P20 Pro, are used at 1800 MHz cellular connection and approximate radiated power of 0.125 W to measure the skin temperature over human head at both, cheek and tilt position for 6 and 30 min calls. The results show that in spite of the direct proportion between the deposited SAR and temperature increase in human tissues, the heat transfer due to thermal conduction may not directly proportional to the SAR, where other factors may play important roles, for example, mobile phone chassis material, heated battery, antenna location inside the mobile phone, and mobile phone position in close proximity to head.